Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences, 2019)
This issue of KIU Journal of Social Sciences focuses on Political Economy, Political Education, Educational Administration, Educational Psychology, Educational Technology as well as Teaching and Learning Skills. The first section of this edition addresses various issues in Political Economy such as health care management, capital market development, city administration, funding tertiary education and barriers to internet shopping among others. The Political Economy deals with the empirical reality, theory, and current governance problems of development, poverty, and inequality. It is through Political Economy that investigations are made into how certain factors influence economic development in a society. Some of these factors may include colonialism, state capacity, regime type, war and conflict, accountability and social structures. Papers in this section x-ray both economic theory regarding development and political science research that highlight the challenges to implementing the policies that would lead to economic development. It was revealed in one of the papers in this section that most tertiary institutions in Nigeria are faced with infrastructural decay as a result of poor funding. The researchers therefore recommended among others the encouragement of private participation, the raising of the education tax collected/or TETFund from 2% to 5% and the revisiting of the practice of Treasury Single Account (TSA) for our tertiary institutions. Section two explores explores Political Education as an instrument of national consciousness. As social beings, men cannot avoid living in groups in order to survive and achieve comfortable living. But the survival and comfort of the individuals depend on how well the socio-political and economic environments of the society are managed. Effective and massive political participation of the citizens in the management of their own affairs are necessary for the political and economic stability of the society. The role of political education in enhancing this stability becomes priceless. Papers, in this second part of the Journal, addresses issues in Political Education such as Nationhood and National Consciousness, Contemporary Vigilantism, Media and Security Education, the Rationality of Mititar Rule, Citizenship Knowledge and so on. One of the papers argues that there is a common chord among the different components of socio-economic and political strides that links national security and eternal vigilance by citizens and agencies of state statutorily empowered to so do and therefore recommends promotion of security must receive the greatest official and individual attention to ensure safety for all citizens through the instrumentality of education and effective media- driven enlightenment. Sections Three, Four and Five which centre on Teaching and Learning Skills as well as Educational Management and Educational Psychology features paper meant to explain how people learn and retain knowledge as well as how to improve the learning process and promote educational success for all students. On the whole, all the papers in this edition of KIU Journal of Social Sciences are interesting and well researched.